Comparing the efficacy of vaginal micronized progesterone gel and capsule for prevention of preterm birth in singleton pregnancies with short cervical length at midtrimester: an indirect comparison meta-analysis - Kabiri, Doron; Hamou, Yael; Gordon, Gali; Ezra, Yosef; Matok, Ilan (Frontiers in Pharmacology, 2023)
Objective: To evaluate the effectiveness of vaginal progesterone in preventing preterm birth in women with a singleton gestation and short cervical length and to determine which of the two formulations, micronized progesterone vaginal capsule versus vaginal gel containing micronized progesterone, is more effective for preventing preterm birth. Data sources: A systematic search was performed in the following databases: EMBASE, PubMed (MEDLINE), The Cochrane Library, and the Clinical Trials Registry (clinicaltrials.gov). Study eligibility criteria: Randomized controlled trials (RCTs), prospective and retrospective observational studies were included. We searched for progesterone administration to prevent preterm birth in asymptomatic women with a shortened cervix (<25 mm) measured by ultrasound in the second trimester of singleton pregnancy. Study appraisal and synthesis methods: Assessments of the risk of bias of RCTs were performed by applying the Cochrane Collaboration’s Risk of Bias Tool; non-randomized control trials were evaluated with the Newcastle–Ottawa Scale (NOS). The primary outcome was preterm birth ≤33 weeks of gestation. Pooled relative risks (RR) and 95% CI’s were calculated for dichotomous outcomes. Heterogeneity of treatment effect was assessed with the I2 statistic. We pooled results of the primary outcome for individual studies using a random-effect model. We then performed a network meta-analysis to pool indirect comparisons between the two formulations (gel vs capsule). This analysis was performed using the network meta-analysis package within the R environment. Results: Five studies met the inclusion criteria (4 RCTs, one cohort study) including 1,048 women. The meta-analysis demonstrated that vaginal micronized progesterone significantly reduces preterm birth risk, Risk Ratio = 0.63; 95% CI, 0.48–0.82; p = 0.0006; with no heterogeneity between the studies: I2 = 0%. In the network meta-analysis, no significant difference was demonstrated (OR = 0.85; 95% CI, 0.43–1.69) between the effect of the two formulations of vaginal micronized progesterone (vaginal gel versus vaginal capsules) on the risk of PTB. Conclusion: Vaginal progesterone is associated with a decreased risk of premature birth in women with a shortened cervix in the second trimester of pregnancy. No differences were found between vaginal micronized progesterone in gel or capsule formulations. Systematic Review Registration: PROSPERO, identifier CRD42020165198.